Assessing the impact of the human resources department’s nurturing connect program on compassion and empathy in physicians and surgeons and its influence on patient advocacy - Solanki, Dhiraj (International Journal of Advances in Medicine, 2024)
Background: Empathy and compassion, key to medical practice, enhance patient adherence to treatments. These traits can be developed, not just inherent. This study implemented the "human resources nurturing connect (HRNC)" program to boost empathy and compassion in healthcare providers, evaluating its impact on patient advocacy over time. Methods: This study was a two-arm, prospective, randomized, single-center conducted from March 2023 to June 2024 at Bhaktivedanta hospital and research institute, Thane, India. Thirty doctors (age 25 to 60) were randomly assigned to intervention and control groups (15 each). The intervention group underwent the HRNC Program to enhance empathy and compassion, measured by the Bhaktivedanta’s index of compassion and empathy in physicians and surgeons (BICEPS) scale, and its effect on patient advocacy assessed by the PAS scale, conducted at baseline, 3, 6, 9, and 12 months. Results: Both BICEPS and PAS scores increased more significantly in the intervention group compared to the control group (p<0.0001). The intervention group’s BICEPS scores rose from 65.47±4.99 at baseline to 83.79±7.19 at 12 months, while the control group showed minimal changes, with scores increasing from 65.48±4.41 to 67.69±5.26. The PAS score in the intervention group also increased significantly (p=0.001) from mean score of 64.48±7.39 to 90.12±10.13, with a percentage change from 21.39% to 39.76%. In contrast, the control group showed a slight increase from 63.53±3.26 to 65.89±3.34, with a percentage change from 0.87% to 3.72%. Conclusions: Study evidenced effectiveness of targeted developmental interventions in fostering empathy and compassion among healthcare providers resulting in better patient outcomes, overall healthcare quality which also translate in patient advocacy.